Model Life Skill Berbasis Potensi Ekonomi Lokal Bagi Mantan Penderita Kusta Sebagai Upaya Pengentasan Kemiskinan - Jurnal Governance Jurnal Kebijakan & Manajemen Publik; Susi Ratnawati; Indah Noviandari (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2011)
Today there has been found 69 leprosy colony at 21 province in Indonesia. This reflects that discrimination is still high. “The settlement of Leprosy is exist because they are afraid return to their society, so they will feel saver if they colonize and live in the community. They are increasingly underdeveloped, abandoned and discriminated. Unfortunately, there are a lot of society living in poverty, so this disease still emerges. Socioeconomic has the main role that’s why this disease is more experienced in poor people than the rich. The study want to review comprehensively about Life Skill Implementation Model based local economy in effort to poverty alleviation for former leprosy in East Java and review the relationship causal factors which influence either related to life education/ability problem or poverty one. The result of the study in the first year are: giving chance and increasing the ability of poor people to former leprosy concerning: the easiness to obtain resources, increasing life skill, the utilization of technological process, utilizing the market continuously, and getting services from other financing process. Life Skill Implementation Model based on Local Economic potential as following: insight, paradigm and mental attitude of learning resident is increased so they able to optimize their own potential, change the challenge to increase their living. The increasing of quality facilitation toward the education program implementation of life skill is to supervise the program so the purpose will be achieved, accompaniment model is developed to support life skill education program, optimize the role in every department to implement and develop life skill program as with characteristic and region potential.